Concatenated hygiene and alienism. The first modern mental hospital in Mexico and the challenges for its construction - Córdoba Flores, Consuelo (2023)
One of the important advances in modern medicine were studies on the nervous system in relation to mental illnesses and, from this new knowledge, its classification was expanded and specified, in addition to its therapeutics revolutionizing by proposing a tripartite treatment: hygienic, moral and pharmacist, either through integration into the daily life of a community, or through confinement in mental health institutions. In this context, concatenated hygiene and alienism set guidelines to define a model of asylums based on the pavilion. The new paradigm spread in Europe and permeated the American continent, emerging various architectural archetypes. This work deals with the vicissitudes experienced to build the first modern mental hospital in Mexico, from the different perspectives of the doctors during the design of the project, to the various conditioning of the sanitary infrastructure required for its operation once built.